"By Hirsute Author": Gender and Communication in the Work and Study of David Foster Wallace. Issue 1 (1st January 2017) - Holland, Mary K.
ABSTRACT: "By Hirsute Author" explores representations of gender and communication in the context of desire in Wallace's work, as one aspect of his abiding concern with the struggle to define self through language, and in order to understand his work's feminist achievements and blindnesses. First, it examines his reading of Wittgenstein's Mistress, finding in his feminist critique of Markson Wallace's own masculinist orientation and sense of complicity with Markson's objectification of Kate. It then considers the Lacanian model of language, desire, and self-definition as employed and critiqued by much of Wallace's fiction, and the ways in which this simultaneous critique/complicity defines the "feminist parody of feminism" of his fiction. Finally, the essay considers the impact on Wallace studies of its relative dearth of attention to gender issues and of input by female scholars.